Application of Internet of Things (IoT) and Big Data in the Maritime Industries: Ship Allocation Model - Mohammad Danil Arifin (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2023)
The Internet of Things (IoT) and Big Data (BD) are growing significantly. IoT is defined as a gateway of technology to digital transformation. To work effectively, BD, Artificial intelligence (AI), and blockchain all rely on those data. Once the physical framework information is changed into computerized digital data, an opportunity opens up to improve vessel operations. Research shows that much of the hidden information can help improve vessel operations by leveraging BD and IoT. Therefore, other sectors of the value chain players such as consignees, shipyards, shippers, manufacturers, and classification societies are also interested in maritime BD. In recent years, the world's ship logistics industry has undergone major changes due to the global shipping cargo movement. The availability of numerous BD is also growing exponentially. This will make it possible to utilize many BDs and IoT in the shipping industry. Successful utilization of these BDs and IoT will bring about major innovations in the shipping industry. In this study, we reviewed several applications of BD and IoT in the maritime domain and developed a ship allocation model using maritime BD and IoT-extracted data. As a result, ship allocation establishment is discussed, and the ship allocation result is evaluated.